THE BONY SUBSTITUTION USING ORTHOTOPIC AUTOCLAVED ALLOGRAFT IN DOGS FEMUR (Sciences & Technologie. C, Biotechnologies, 2010)
Implantation of different lengths of orthotopic autoclaved allograft in the femur of dogs fixed withintramedullary pin and stainless steel wire has been performed in 11 dogs, to determine the maximumpercentage of bone substitution, as well as, comparison of fenestrated and non fenestrated bony implants.Clinical lameness and serial post operative radiographs are evaluated. Bone union in five dogs, breakingof the implant in three cases and death of two dogs during the follow up has been observed. Themaximum percentage of the bony substitution that could be applied successfully is about 33% with themaximum length of 6 cm. The rapid hard callus formation has been observed due to the use of perforatedimplant